KEANEKARAGAMAN MARGA Nothaphoebe Blume, SUKU LAURACEAE (MEDANG - MEDANGAN) DARI PROVINSI LAMPUNG, KOLEKSI HERBARIUM BOGORIENSE (BO) - Fersiana Riska Devilia; Yulianty -; Sri Wahyuningsih; Deby Arifiani (Floribunda, 2023)
Nothaphoebe Blume is a genus of the Lauraceae or Medang-medangan family, and is included in the Persea subgroup together with the genera Alseodaphne, Dehaasia, Persea, and Phoebe. Information on the diversity of Nothaphoebe in Sumatra, especially in Lampung province, has never been reported. Therefore, the aim of this study was to understand the morphological characters and species of Nothaphoebe occured in Lampung. The morphological characters observed included twigs, leaf shape, flowers, and fruits. The results of morphological characterisation show that there are five species of Nothaphoebe, i.e., Nothaphoebe falcata, Nothaphoebe foetida, Nothaphoebe macrocarpa, Nothaphoebe magnifica, and Nothaphoebe umbelliflora. Identification key for species, descriptions of each species and distribution maps are presented in this article. Keywords: Herbarium Bogoriense, Lauraceae, Morphology, Nothaphoebe, Lampung Province